First record of leucism in brown pelicans (Pelecanus occidentalis) in Costa Rica - Vargas-Masís, Roberto (2014)
Leucism in birds is rarely observed in the Pelecaniformes order and has not been recorded for the brown pelican (Pelecanus occidentalis) in Costa Rica. We describe an observation of a leucistic brown pelican with white plumage, pink coloration on the bill and feet, but normal color on the eyes. Leucism in birds is the most frequently reported color aberration and these cases present low survival rates for individuals. Although isolated cases occur in birds, these reports help determine the frequency of these events for spe cific bird populations and species.